MAQASHID SYARIAH DALAM PERSPEKTIF YUDIAN WAHYUDI DAN IMAM AL-SHATIBI: Studi Perbandingan Pemikiran Ushul Fikih - Alfikri, Ahmad; Aznan Siregar, M. Asgaff; Sadari, Sadari (Moderation | Journal of Islamic Studies Review, 2026)
The debate on the maqashid of sharia between the approaches of Al-Shatibi and Yudian Wahyudi has significant implications for the development of ushul fiqh and Islamic law in Indonesia, both theoretically and practically. Indonesia, as a modern, pluralistic, constitutional, and non-religious nation-state, faces unique challenges in integrating Islamic values into the national legal system without falling into the trap of sharia formalism or extreme secularization. Theoretically, Al-Shatibi's approach makes an important contribution to strengthening the methodological legitimacy of maqashid in the study of ushul fiqh in Indonesia. The istiqra' framework and the hierarchy of maqashid (daruriyat, hajiyat, tahsiniyat) provide a relatively stable epistemological foundation that is acceptable across schools of thought. In an academic context, this framework serves as a normative anchor that prevents maqashi from being reduced to value-free ethical discourse. However, this approach needs to be criticized and further developed to avoid reproducing classical ushul fiqh. In the Indonesian context, characterized by democracy, legal pluralism, and modern sociopolitical dynamics, Al-Shatibi's maqashid risks losing its analytical power if it is not contextually reconstructed. This is where Yudian Wahyudi's theoretical contribution becomes relevant, particularly in establishing maqashid as a critical epistemological paradigm for historical fiqh products. Yudian's approach encourages a shift in ushul fiqh from merely a science of derivation to a science of evaluation, namely a science that not only produces law but also assesses the justice, rationality, and relevance of that law in the context of the modern state. This theoretical implication is crucial for the development of ushul fiqh in Indonesia to avoid being trapped in the dichotomy between “normative Islamic law” and “positive state law.” Theoretically, the development of maqashid sharia in Indonesia demands a methodological synthesis: maqashid must remain rooted in the ushul fiqh tradition (as inherited by Al-Shatibi), but also be developed as an instrument of epistemological criticism of social and legal realities (as pioneered by Yudian). This synthesis paves the way for the emergence of contextual Indonesian ushul fiqh (Islamic jurisprudence) with scientific legitimacy and social relevance. Practically, the debate on the principles of Islamic jurisprudence (maqasid) has a direct impact on legislative practices, religious courts, and religious fatwas in Indonesia. In the realm of legislation, the maqasid approach contributes to national law without having to be embodied in the symbolic and formal form of sharia. The principles of protecting religion, life, intellect, property, and descendants can be translated into constitutional norms such as human rights, social justice, and general welfare.